The effect of Piper betle on wound healing in male Sprague Dawley rats - Nur Ain J,; Ainaa Diyana S,; Nur Hazirah R,; Nur Fathiah AS,; Fairus Ahmad,; Teoh, SL; Yasmin Anum Mohd Yusof, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Piper betle (PB) leaves have been traditionally used in many Asian countries for the healing of wounds and other ailments. The aim of this study was to examine the wound healing effect of PB on skin injury-inflicted Sprague-Dawley rats. Eighteen male Sprague-Dawley rats were inflicted with wounds and then divided into three groups consisting of a control (normal wound healing without dressing), saline (wound healing aided by gauze soaked in saline) and PB (gauze impregnated with PB paste) dressings. Wounds were created on the back of rats with 6-mm sterilized punch biopsy needle. Wounds were examined on days 3, 5, 7, 9, 11 and 13 for dryness, exudation, and scar formation. Rats were sacrificed on day 14 and the granulation tissue formed on the wound was then excised for histological examination using Hematoxylin and Eosin staining. The formation of granulation tissue in rats treated with PB showed higher progress to wound closure with shorter days (on day 3) compared to the control and saline group (on day 5). PB dressing minimized the formation of scar tissue significantly (p<0.05) compared to the control and saline groups. In conclusion, our results suggest that PB has good wound healing effect with less scarring and perhaps it can be used to treat wound complementary to the present method.